(3QHjY GdaDGO aj JQJjH UdhGJ GdWQjb hGdChQGOs - (3GdTQbGhj, YHO Gddg Hf MLGRj, J(B1227(3g`s ((3YHO Gddg MLGRj GdTQbGhjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfCeG HYO ajbhdYHO Gddg Hf MLGRj GdeTghQ HGdTQbGhjCf ChVM dge Pdc abjOJ aj gPg GdChQGb eG CNPJg Yf GdYGQa HGddgeMeO GdcQOj GdchQGfj hSejJg QHjY GdaDGOs
(3BNQgG (B:s
(3hJQJjH PcQ gPg GdCSeGA Ydi MSH JQJjHgG hVYg GdLfjO HWQjb GdcTa hJHYg ef HYOg ef GdeTGjNs
(3HNW eDdags
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 78s
(3eYLe GdeDdajf(B: 2 / 234s
(3EjVGM Gdecfhf(B: 1 / 548s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs